Study of Ge-Sb-Te Superlattice Structure Based on Topological Descriptors - Xiujun Zhang; Muhammad Naeem; Abdul Rauf; Adnan Aslam; Zafar Iqbal; Abudulai Issa (Journal of Mathematics)
Ge-Sb-Te superlattice is a new electronic material that is capable of storing nonvolatile phase-change memories with very low energy consumption. Topological descriptors are numerical values given to molecular structures that may be used to predict specific physical/chemical characteristics. In this work, we have investigated topological descriptors of the Ge-Sb-Te superlattice structure based on ev and ve-degree. We have calculated the Zagreb, geometric-arithmetic, Randic, and atom-bond connectivity indices of the Ge-Sb-Te superlattice structure using the ev- and ve-degrees. This kind of research may be beneficial for understanding the structure’s chemical and biological activity.